2011
DOI: 10.3747/co.v18i3.751
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Experience with Adjuvant FEC-D Chemotherapy in Four Ontario Regional Cancer Centres

Abstract: than in those who did not [15/235 (6.4%) vs. 137/436 (31.4%); p < 0.001; risk ratio: 0.20]. ConclusionsIn routine clinical practice, treatment with fec-d is associated with a higher-than-expected rate of febrile neutropenia, in light of which, primary prophylaxis with growth factor should be considered, per international guidelines. Adoption based on clinical trial reports of new therapies into mainstream practice must be done carefully and with scrutiny.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 22 publications
2
24
1
Order By: Relevance
“…The incidence of febrile neutropenia in the bcirg 001 tac arm was 24.7% 6 , which is similar to that in our small tac group not receiving primary prophylaxis. The incidence of febrile neutropenia in the pacs-01 fec-d arm for cycles 4-6 was 7.4% 8 , which was lower than that observed in our population (17.6%), and much lower than the 51.3% reported in a large retrospective study 12 .…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The incidence of febrile neutropenia in the bcirg 001 tac arm was 24.7% 6 , which is similar to that in our small tac group not receiving primary prophylaxis. The incidence of febrile neutropenia in the pacs-01 fec-d arm for cycles 4-6 was 7.4% 8 , which was lower than that observed in our population (17.6%), and much lower than the 51.3% reported in a large retrospective study 12 .…”
Section: Discussioncontrasting
confidence: 51%
“…The bcirg 001 study 6 and retrospective analyses 10 suggest that tac is associated with a significant risk of febrile neutropenia (particularly in the absence of primary g-csf support) and hospitalization. And although pacs-01 reported a relatively low incidence of febrile neutropenia 8 , retrospective studies have documented much higher rates of febrile neutropenia and hospitalization 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…The population-based retrospective data presented by Madarnas et al 2 demonstrate an unexpectedly high rate of fn that raises important questions about how fec-d should be used and whether primary growth factor support has a role to play. Further efforts are needed to better understand how novel therapies are used in the general population and whether they translate to outcomes that are comparable to those reported in the relevant clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Madarnas et al 2 serves as an example of how population-based data can augment knowledge of new medical therapies. In 2006, the results of pacs-01 were published, establishing the improved efficacy of fec-d adjuvant chemotherapy compared with standard fec-100 3 .…”
Section: Paper By Madarnas Et Al and Pacs-01mentioning
confidence: 99%
“…This study had 671 patients who utilized the FEC-D regimen and showed a TRD rate of 0.4% and a FN rate of 22.7% (Madarnas et al, 2011). The authors concluded that primary usage of haematopoietic growth factor should be considered in view of the high FN rate.…”
Section: Introductionmentioning
confidence: 99%